2023
DOI: 10.3389/fpls.2023.1282718
|View full text |Cite
|
Sign up to set email alerts
|

Candidate regulators of drought stress in tomato revealed by comparative transcriptomic and proteomic analyses

Minmin Liu,
Gangjun Zhao,
Xin Huang
et al.

Abstract: Drought is among the most common abiotic constraints of crop growth, development, and productivity. Integrating different omics approaches offers a possibility for deciphering the metabolic pathways and fundamental mechanisms involved in abiotic stress tolerance. Here, we explored the transcriptional and post-transcriptional changes in drought-stressed tomato plants using transcriptomic and proteomic profiles to determine the molecular dynamics of tomato drought stress responses. We identified 22467 genes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…The findings showed that the GCK vs. G100 group and GCK vs. G500 group dominantly showed common enrichment terms, including the response to oxidative stress and the defense response. Highly similar results were reported by Zhang et al, showing that oxidative stress may be a coping mechanism for soybean to resist negative external stimuli [53,54]. Specifically, the hydrogen peroxide catabolic process was enriched in the GCK vs. G100 group.…”
Section: Enrichment Analysis Of Differential Genessupporting
confidence: 87%
“…The findings showed that the GCK vs. G100 group and GCK vs. G500 group dominantly showed common enrichment terms, including the response to oxidative stress and the defense response. Highly similar results were reported by Zhang et al, showing that oxidative stress may be a coping mechanism for soybean to resist negative external stimuli [53,54]. Specifically, the hydrogen peroxide catabolic process was enriched in the GCK vs. G100 group.…”
Section: Enrichment Analysis Of Differential Genessupporting
confidence: 87%
“…High-throughput techniques for omics-based analyses may be combined to elucidate the mechanisms regulating complex plant traits, including drought stress resistance in tomatoes, which is controlled by diverse factors. Only a few studies have been conducted on tomato drought tolerance and recovery [34][35][36][37][38][39]. Consequently, differences in gene expression and metabolite contents between tomato cultivars and wild species are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These changes in phenotypic traits over short timescales are driven by differential gene expression, which can be measured by assessing the expression levels of mRNA found in plant tissues (Shanker et al 2014). Differential expression analyses comparing water-stressed plants with controls have identi ed candidate genes relating to acclimation under short-term drought stress in a wide range of species, including oak (Gugger et al 2017), poplar (Yang et al 2023) and pine (Li et al 2024), as well as annual plants such as maize (Le et al 2012) and tomato (Liu et al 2023). Recent advances in nextgeneration sequencing technology can yield large quantities of mRNA sequence data in a short time period (RNA-seq), and thus provide a cost-e cient and powerful tool for differential expression analyses (Deshpande et al 2023).…”
Section: Introductionmentioning
confidence: 99%